Lean Six Sigma Integration with VALSAT and FMEA Methods for Waste Identification in PT. X - Bambang Sutejo; Moh. Ainul Fais; Dedy Kunhadi (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
This study identifies and reduces waste in the cooking oil production process at PT X by integrating Lean Six Sigma with Value Stream Analysis Tools (VALSAT) and Failure Mode and Effects Analysis (FMEA). VALSAT is used to classify value-added and non-value-added activities, while FMEA prioritizes waste based on Risk Priority Number (RPN). The results show that defects are the most dominant waste (RPN 294), followed by waiting and inventory. Process mapping reveals a total lead time of 370 minutes, in which 60 minutes are non-value added. Improvement recommendations include scheduling preventive maintenance, aligning raw material orders with actual demand, optimizing operator coordination, applying FIFO in inventory handling, and increasing transportation efficiency. This integrative approach provides a structured method for identifying critical waste sources and supports operational efficiency improvement in food-processing industries.